Analisis Kinerja Konsultan Manajemen Konstruksi Proyek EPC pada Pembangunan Fasilitas Pengolahan Batu Bara di Tanjung Enim, Sumatera Selatan - Brillianto, Ananta Giga; Priyambodo, Bambang; Naibaho, Pio Ranap Tua; Sembiring, Kristina (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
Engineering, Procurement, and Construction (EPC) projects face complex challenges such as multidisciplinary coordination, tight schedules, material procurement risks, and design change dynamics, which require the crucial role of Construction Management Consultants (CMCs) in ensuring the achievement of time, cost, and quality targets. This study analyzes the influence of expert competence, quality management, and communication on CMC performance in the coal processing facility construction project in Tanjung Enim, South Sumatra. The study employs a quantitative approach using research instruments developed based on indicators of expert competence, quality management, and communication. Instrument validation was conducted using item analysis with Pearson's product-moment correlation coefficient, while reliability was measured using Cronbach's Alpha coefficient. Data were analyzed using partial correlation and multiple regression techniques. The results of the study indicate: (1) Expert competence has a significant positive effect on KMK performance (ry1 = 0.377 > 0) with the regression equation Ŷ = 19.843 + 0.144 X1; (2) Quality management has a significant effect (ry2 = 0.543 > 0) with the equation Ŷ = 19.040 + 0.174 X2; (3) Communication makes an important contribution (ry3 = 0.471 > 0) with the equation Ŷ = 19.590 + 0.152 X3. Multiple regression analysis shows that the three variables together explain 82% of the variance in performance (ry123 = 0.9272 > 0) with the equation Ŷ = 3.9547 + 0.200 × X1 + 0.1995 × X2 + 0.2237 × X3. These findings confirm that the performance of construction management consultants on EPC projects is significantly influenced by expert competence, quality management, and communication. The study recommends the need for standardization of competencies, implementation of an integrated quality management system, and development of an effective communication model to improve the performance of CMC on similar projects.